2012
DOI: 10.1089/fpd.2011.1010
|View full text |Cite
|
Sign up to set email alerts
|

Bacteriological Quality of Raw Milk Used for Production of a Brazilian Farmstead Raw Milk Cheese

Abstract: The objective of this study was to evaluate the bacteriological quality of raw cow's milk utilized for the production of Traditional Minas Serro cheese, a Brazilian farmstead raw milk cheese. Raw milk samples were collected from six farmstead cheese operations manufacturing raw milk cheese from cow's milk. Coliform count (CC) and Escherichia coli counts were determined using Petrifilm™ EC plates, and Staphylococcus aureus counts were determined using Petrifilm™ Staph Express count plates. The standard plate co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
12
0
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(14 citation statements)
references
References 40 publications
1
12
0
1
Order By: Relevance
“…These results thus reinforce the reported by Costa Sobrinho et al (2012) that the poor hygiene promotes the establishment and the circulation of microorganisms between animals of the herd, especially when good management practices are not commonly used.…”
Section: Resultssupporting
confidence: 90%
See 1 more Smart Citation
“…These results thus reinforce the reported by Costa Sobrinho et al (2012) that the poor hygiene promotes the establishment and the circulation of microorganisms between animals of the herd, especially when good management practices are not commonly used.…”
Section: Resultssupporting
confidence: 90%
“…This diversity was expected, since when dispersed in the environment, the occurrence of genetic exchange between different bacteria population can be enhanced. These microorganisms are subjected to adverse conditions (Costa Sobrinho et al 2012, Lopes et al 2012) instead of particular epidemiological situations, as shown by the fact there were no shared profiles between farms or the municipalities visited. This is the first study evaluating the genetic relationship of E. coli sub-populations isolated from mastitic milk and from flies.…”
Section: Resultsmentioning
confidence: 99%
“…However, there was no detection of this group of microorganisms in pasteurized milk samples (<0.3MPN mL -1 ), showing the pasteurization effectiveness process used by the dairies evaluated, which was confirmed by results of phosphatase (negative) and peroxidase (positive) tests. High levels of thermotolerant coliforms reported in raw milk samples analyzed can be related to deficient sanitary conditions of dairy farms or to hygienicsanitary problems in the milking process (MORAES et al, 2009;SOBRINHO et al, 2012;GALINARI et al, 2014;PIERI et al, 2014). Bacteria belonging to group of thermotolerant coliforms colonize mammals' intestine and their detection can indicate the presence of other pathogenic microorganisms of enteric origin.…”
Section: Resultsmentioning
confidence: 99%
“…Coagulasepositive Staphylococcus aureus is one of the most common pathogens infecting dairy cows and a major causative agent of mastitis. This microorganism is commonly isolated from raw milk and represents a potential risk for public health due to the possibility of staphylococcal toxin production (SOBRINHO et al, 2012). S. aureus, the main species of the CPS group, can produce toxin when it reaches 10 5 to 10 6 CFU per gram of food.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation